ENSURING OPTIMUM MOVEMENT ACTIVITY USED TOOLS AND THE METHODOLOGY OF THEIR APPLICATION (Neo Science Peer Reviewed Journal, 2023)
This is it in the article In the model program of preschool children's institutions, it is recommended to use the simplest elements of swimming and water games, walking, running, throwing, jumping, movement games and sports games that develop various physical qualities and preparatory exercises to increase movement activity. Accordingly, we have focused below on the tools that should be used to ensure the activity of the movement.